Search for new color-octet vector particle decaying to tTtopbar in pPtopbar collisions at √s=1.96 TeV - Aaltonen, T; Adelman, J; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We present the result of a search for a massive color-octet vector particle, (e.g. a massive gluon) decaying to a pair of top quarks in proton-antiproton collisions with a center-of-mass energy of 1.96 TeV. This search is based on 1.9 fb-1 of data collected using the CDF detector during Run II of the Tevatron at Fermilab. We study tTtopbar events in the lepton. +. jets channel with at least one b-tagged jet. A massive gluon is characterized by its mass, decay width, and the strength of its coupling to quarks. These parameters are determined according to the observed invariant mass distribution of top quark pairs. We set limits on the massive gluon coupling strength for masses between 400 and 800 GeV/c2 and width-to-mass ratios between 0.05 and 0.50. The coupling strength of the hypothetical massive gluon to quarks is consistent with zero within the explored parameter space. © 2010 Elsevier B.V.